Welfare implications of joining a common currency - Michele Ca' Zorzi; Roberto A. De Santis; Fabrizio Zampolli (European Central Bank (ECB), 2005)
This paper examines the welfare implications of a country joining a currency union as opposed to operating in a flexible exchange rate regime. At the country level, the suboptimal response to domestic and foreign shocks and the inability of setting inflation at the desired level may be offset by a positive impact on potential output. We show that for entry to be welfare enhancing, the potential output gain must be the larger, the smaller the country, the larger the difference between the standard deviation of supply shocks across the participating countries, the smaller the correlation of countries' supply shocks and the larger the variance of real exchange rate shocks.
Keywords: E52; E58; F33; F40; 330; Balassa-Samuelson Effect; Currency union; monetary policy; Welfare; Währungsunion; Mitgliedschaft; Wohlfahrtsanalyse; Geldpolitik; Theorie; Balassa-Samuelson-Effekt